Making a place special—The development of Restorative Marine Ecotourism at a dive destination village - Ferretti, Eliana; Lewis, Nicolas I.; Thrush, Simon F.; Lucrezi, Serena; Hillman, Jenny R. (Frontiers in Sustainable Tourism, 2023)
Marine ecotourism is a multifaceted social-ecological activity that seeks to balance economic benefits with support for sustainability and positive ecosystem impacts. Successful marine ecotourism relies upon ecosystem health and has the potential to restore or regenerate nature. Restoration efforts of marine habitats aim to foster social and ecological resilience, requiring novel management strategies. To date examples of successful restorative tourism are rare in marine habitats. It is early days, emphasizing the importance of exploring opportunities for the development of restorative practices. To help frame opportunities for the development of Restorative Marine Ecotourism (RME), this study explores the relationship between ecological restoration initiatives and marine ecotourism in the New Zealand village of Tutukaka. This qualitative study assessed stakeholders' perspectives of opportunities and challenges to develop local RME initiatives in Tutukaka, where development has been strongly influenced by the possibility to access a nearby offshore marine reserve and internationally famous dive site. Data were obtained from semi-structured interviews with marine ecotourism businesses, ecological restoration actors, and governance authorities, and analyzed through thematic analysis. The interviews identified a set of core social-ecological relationships around which strategies to guide the development of RME coalesce: ongoing coastal and marine environmental issues and the discussion around how best to address them; opportunities to develop local restoration initiatives; economic and ecological challenges to realizing those opportunities; and the costs, benefits and opportunities of RME. Interview respondents emphasized the importance of diverse approaches to address the challenges around RME development, including collaboration among stakeholders, the willingness to experiment widely around experiential learning and take risks, and importantly adopting strategies to make places “special.” This study offers insights that can inform the planning and implementation of RME initiatives at a local scale to support the achievement of both ecological restoration goals and sustainable tourism practices. These include trusted relationships among stakeholders, fostering bottom-up processes, and the value of producing social-ecological knowledge. The Tutukaka case highlights possible avenues for restoration to effectively contribute to marine ecotourism. The focus on the “specialness of place” highlights the importance of place-based knowledge and preservation that facilitates trust, entrepreneurialism, environmental ethics, and supportive management.